From Local Crafts to Market Niches: The Marketing Potential of Artisanal Foods in Ukraine - Yuriy Danko; Viktoriya Kolodiazhna; Olena Nifatova; Anhelina Halynska; Kseniia Bliumska-Danko; Oleksandr Kovbasa; Liuba Turchyn (Foods)
This study explores the marketing potential of artisanal agri-food products in Ukraine by examining their structural, regional, and consumer dimensions. Amid growing interest in sustainable and locally rooted food systems, the research addresses how artisanal production can evolve from informal crafts to market-recognized value. This study is based on an analysis of official statistical data and an analysis of registered artisanal food producers in specific areas in Ukraine. It emphasizes the role of household-based agriculture in securing raw materials, the impact of cultural–tourism infrastructure on product visibility, and the benefits of self-sufficiency in raw material sourcing for product differentiation. The findings reveal that regions with stronger household production and cultural engagement demonstrate higher activity in the artisanal food sector. This study concludes that artisanal food production offers a viable pathway for regional development, rural resilience, and the strengthening of local food identity.